The Effect Of Sports Massage Treatment On Knee Pain Relief In Sports Activities Aged 40-60 Years - Fahreza Dwi Nugroho; Joesoef Roepajadi; Dita Yuliastrid; A Burhanuddin Kusuma Nugraha (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Knee pain is a condition in which a person experiences a sensation of pain in the knee area during activities such as walking, engaging in physical activity, or even while at rest. Sports massage is a manual or mechanical manipulation technique using the hands on the soft tissues of the body, aimed at eliminating metabolic waste products in the muscles, such as lactic acid. Massage can improve blood circulation within the muscles, contributing to increased oxygen transport and accelerating the body's metabolic processes. This study uses a pre-experimental method to assess the effectiveness of sports massage treatment in reducing knee pain. The research design employed is a one-group pretest-posttest design. The population in this study consists of males and females aged 40–60 years in Depok City. The sampling technique used is non-probability sampling with purposive sampling. The research instrument used is the Visual Analog Scale (VAS), with a scale range from 0 to 10. Data analysis began with prerequisite testing using the one-sample Kolmogorov-Smirnov test before conducting the paired sample t-test. Based on the Kolmogorov-Smirnov normality test results, the Sig. value for the pretest was 0.200 and for the posttest was 0.090. Since both Sig. values are greater than 0.05, it can be concluded that the pretest and posttest data are normally distributed. Based on the paired sample t-test results, the average difference between the pretest and posttest scores was 3.933, indicating an improvement of 3.933 points. The Sig value (2-tailed) is 0.000, which indicates that the difference between the pretest and posttest is statistically significant. Based on the research results and discussion above, it can be concluded that sports massage is effective in reducing knee pain in physically active individuals aged 40–60 years.